2007
DOI: 10.1038/sj.onc.1210711
|View full text |Cite
|
Sign up to set email alerts
|

A role for iron in Wnt signalling

Abstract: There is an emerging body of evidence implicating iron in carcinogenesis and in particular colorectal cancer, but whether this involves Wnt signalling, a major oncogenic signalling pathway has not been studied. We aimed to determine the effect of iron loading on Wnt signalling using mutant APC (Caco-2 and SW480) and wild-type APC (HEK-293 and human primary fibroblasts) containing cell lines. Elevating cellular iron levels in Caco-2 and SW480 cells caused increased Wnt signalling as indicated by increased TOPFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 37 publications
(49 reference statements)
1
101
0
Order By: Relevance
“…(P)RR and v-ATPase were shown to be required to mediate Wnt signaling during antero-posterior patterning of Xenopus early central nervous system development. There has been accumulating evidence which shows the close relationship among iron, the Wnt signaling and erythropoiesis (Brookes et al 2008;Tarafdar et al 2013). Canonical Wnt/β-catenin signaling plays important roles in mesodermal specification, primitive erythropoiesis and early hematopoietic progenitor formation during hematopoietic induction (Tarafdar et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(P)RR and v-ATPase were shown to be required to mediate Wnt signaling during antero-posterior patterning of Xenopus early central nervous system development. There has been accumulating evidence which shows the close relationship among iron, the Wnt signaling and erythropoiesis (Brookes et al 2008;Tarafdar et al 2013). Canonical Wnt/β-catenin signaling plays important roles in mesodermal specification, primitive erythropoiesis and early hematopoietic progenitor formation during hematopoietic induction (Tarafdar et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Canonical Wnt/β-catenin signaling plays important roles in mesodermal specification, primitive erythropoiesis and early hematopoietic progenitor formation during hematopoietic induction (Tarafdar et al 2013). Brookes et al (2008) speculated that iron-medicated Wnt signaling and c-myc induced expression of transferrin receptor 1. We therefore could not deny the possibility that the Wnt/β-catenin signaling acts in cooperation with (P)RR, v-ATPase and mTORC1 in erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is involved especially in oxygen transport, DNA synthesis, oxidative phosphorylation, and cell cycle progression, and all of them have a role in carcinogenesis Brookes et al, 2008;Coombs et al, 2012). The potential cytotoxic activity of iron complexes appears to be related to the redox reactions occurring between Fe(II) and Fe(III) in physiological conditions (Jungwirth et al, 2011).…”
Section: Ironmentioning
confidence: 99%
“…In the background of an elevation in the cellular iron import proteins such as transferrin receptor 1 and Divalent metal transporter 1, this culminates in cellular iron accumulation; a phenotype which we have previously reported in colorectal cancer [14] . Furthermore, we have recently demonstrated that elevating intracellular iron in the presence of mutations in either adenomatous polyposis coli (APC) or β-catenin results in increased Wnt signalling; the major oncogenic signalling pathway in the colon [9,10] . Thus hepcidin expression at the level of the tumour may be a mechanism of ultimately accentuating carcinogenesis and that abrogating hepcidin expression either directly or indirectly through IL-6 may provide a strategy for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Increased hepcidin levels are likely to also cause an accumulation of iron in other ferroportin expressing cell lineages such as colonocytes. Our recent studies have shown that raising colonocyte iron levels can result in increased Wnt signalling which has been shown to be crucial in colorectal carcinogenesis [9,10] . However, to date there are no studies addressing whether hepcidin expression contributes to the anaemia in colorectal cancer and whether hepcidin itself may be considered a pro-oncogenic factor.…”
Section: Introductionmentioning
confidence: 99%